Analysis of the Possibility of Ice Melting Intensity Monitoring by Direct Current in High-Voltage Electrical Systems - E. S. Moloshnaya; V. V. Nechitailov; I. V. Melnikov; S. A. Baran (Глобальная ядерная безопасность)
The Rostov nuclear power plant is the largest energy center in the South of Russia. Electricity from the nuclear power plant is transmitted to nodal substations across the territory of the Southern region, the climatic conditions of which contribute to the formation of ice deposits on power lines, this determines the urgency of the problem of ice melting. Existing systems for early detection of ice and melting it on wires of 110-500 kV overhead lines allow preventing wire breakage and destruction of supports. In modern methods ice melting is performed with alternating and direct current using special transformers and rectifiers with a melting voltage of 10 kV and a melting current of up to 3600 A, currents and voltages to prevent overheating of contacts in melting circuits and compliance with melting parameters. In circuits using direct current, there is no reliable method for controlling its magnitude. The paper considers the possibility of using a fiber-optic current sensor with a measurement range from 1 to 3600 A.